الترجمة وفضلها في عالمية ابن رشد - بحري صديق (University Of Eloued جامعة الوادي, 2022)
نسعى في بحثنا الى تقديم أهم أساليب الترجمة في العلوم الاجتماعية والإنسانية و دورها في التعريف بابن رشد للعالم وفهم فلسفته ، ونخص بذالك مترجميه من الفلاسفة والمفكرين اليهود واللاتينيون ، خاصة ما تعلق فيها بفلسفته العلمية وبأصل العالم ووجود الله وكذا علاقة الفلسفة بالدين وغيرها من القضايا الابستيمولوجية ،التي شغلت حيزا واسعا من الجدل ،فبعد أن أصيبت مؤلفات ابن رشد بالضياع والتنكيل عادت مجددا بفعل الترجمة فيما بعد وبقوة فكرا منيرا للعقول تتباهى بدراسته أكبر الجامعات العالمية ، فقد أرست ترجمة شروحه على أرسطو الى اللاتينية لعدة عقود لتصبح جزءا من التراث الارستوطاليسي في أوروبا كلها ، ولكن رغم ذالك فإنهم لم يوفوا بترجمة فلسفته وفكره الأصيل ، سواء جهلا منهم بمبادئ الترجمة الفلسفية أم عمدا وذالك لما كان يضمره الغرب للشرق من حقد ،حيث شوّهت أفكاره وطمست مبادئه الاساسية . Abstract : The intervention of our research prompts us to present the most important methods of translation in the social and human sciences and its role in introducing ibn Rushd to the world and understanding his philosophy,Our research intervention leads to the presentation of the most important results of translation problems in the social and human sciences and the extent of their impact on the originality and understanding of ibn Rushd's philosophy, and especially his translators of Jewish and Latin philosophers and thinkers, especially what relates to his scientific philosophy and the origin of the world and the existence of God as well as the relationship of philosophy to religion and other epistemological issues, which occupied a wide area of controversy, after ibn Rushd's writings were lost and abused again by translation later and strongly a enlightened thought of the minds boasting of studying the largest universities in the world, The translation of his commentaries on Aristotle into Latin was established for several decades to become part of the Aristotlesian heritage in all of Europe, but nevertheless they did not live up to the translation of his philosophy and original idea, whether ignorant of the principles of philosophical translation or deliberately and that of the hatred that the West had in the East, where his ideas were distorted and his basic principles were obliterated.
Translation and its role in the universality of Ibn Rushd
مداخلة
Keywords: الترجمة; ابن رشد; العالمية; العلوم; الابداع; الحوار; الحضارة; translation; Ibn Rushd; science; creativity; dialogue; civilization; morality; universality.